Peptide antagonists of the plasmodesmal macromolecular trafficking pathway - Kragler, Friedrich (Oxford University Press, 2000)
In plants, cell-to-cell transport of endogenous and viral proteins and ribonucleoprotein complexes (RNPCs) occurs via plasmodesmata. Specificity of this transport pathway appears to involve interaction between such proteins/RNPCs and plasmodesmal chaperones/receptors. Here, KN1 and the cucumber mosaic virus movement protein (CMV-MP) were used, in a modified phage-display screening system, to identify peptides capable of interacting with proteins present in a plasmodesmal-enriched cell wall fraction. Binding/competition assays and microinjection experiments revealed that these phage-displayed peptides and homologous synthetic oligopeptides function as ligand-specific antagonists of macromolecular trafficking through plasmodesmata. A KN1 peptide antagonist had the capacity to interact with a motif involved in the dilation of plasmodesmal microchannels. Although KN1 could still achieve limited movement through plasmodesmata when this SEL motif was blocked, KN1-mediated transport of KN1–sense RNA was fully inhibited. These findings provide direct support for the hypothesis that KN1 requires, minimally, two physically separated signal motifs involved in the dilation of, and protein translocation through, plasmodesmal microchannels, and provide direct proof that plasmodesmal dilation is a prerequisite for the cell-to-cell transport of an RNPC.